The complex relationship between welfare and reproduction in cattle. (11th September 2019) - Ritter, Caroline; Beaver, Annabelle; von Keyserlingk, Marina A. G.
Abstract: Using reproduction parameters as indicators for cattle welfare has limitations and, at best, these parameters should only be viewed as indirect indicators of welfare. On a farm level, measures such as fertility rates emphasize biological performance of the herd but fail to consider the welfare of individual animals. Even on an individual level, the relationship between reproductive effectiveness and animal welfare is complex. Good reproductive performance does not automatically signify good welfare, as domestication and targeted breeding programmes have led to prioritization of high productive and reproductive performance in most modern farm animal species. In this review, we synthesize literature regarding cattle husbandry, reproduction, welfare and their multidimensional relationships. We argue that practices such as artificial insemination or the use of sexed semen may provide potential welfare advantages as these practices reduce the risk of disease transmission and injury or enable selection of specific beneficial traits. Furthermore, they may offer a solution to current practices jeopardizing welfare, such as the management of surplus bull calves in the dairy industry. Conversely, the animals' ability to perform natural behaviours such as oestrous expression, an aspect arguably contributing to welfare, is often limited on commercial farms; this limitation is particularly evident in housing systems such as tie stalls where movement is restricted. Moreover, common management practices such as oestrus manipulation may lead to negative attitudes in citizens who often regard naturalness as important element of animal welfare.